Geo-analytical hierarchy process for flood risk mapping using moderate resolution of satellite images - Syarifuddin, Misbari; Gisen, Jacqueline Isabella Anak; Amir Asyraf, Mohd Fauzi; Nur Aizah, F.M. Rosli (Institution of Engineering and Technology, 2022)
Career prospect, education and facilities attract more people gravitate toward urban areas. The population rate has increased significantly, placing a demand on metropolitan regions which become major drivers of natural hazard growth, including flood events. Satellite technology offers good services for flood mitigation and provides precautionary measures in a particular area. Thus, this study aims to produce flood risk map area in Kuantan using moderate- resolution satellite images and Digital Elevation Model (DEM) dataset was integrated with GIS tools to conduct flood risk analysis. The study found that the Kuantan city centre with low drainage capacity and high paved area is the highest risk flood zone, whereas Gambang with a huge green corridor and good drainage system is the lowest risk flood zone. These findings can provide the communities in this area with the required details and understanding of the type of floods normally occurring in study areas. This study is crucial to propose a solution to mitigate flood occurrences based on the satellite-based risk map analysis. This study supports the agenda of SDG13: Climate Action; where flood risk analysis serves to determine awareness and early warning to prevent loss of human life, biodiversity, crops and damage to property.